The Effectiveness of Temporary Hemiepiphysiodesis for Non‐idiopathic Coronal Angular Deformity of the Knee in Children: A Comparison of Hinge Eight‐Plate and Traditional Eight‐Plate - Zhen‐Zhen Dai; Tai‐Chun Li; Han Zhou; Qin Zhang; Hai Li (Orthopaedic Surgery)
Abstract Objective Temporary hemiepiphysiodesis (TH) is a very common technique for coronal angular deformity of the knee in children, especially non‐idiopathic. However, there is currently a dearth of comparative research on the hinge eight‐plate (HEP) and traditional eight‐plate (TEP). This study aimed to assess the clinical effectiveness and implant‐related complication rates of TH using TEP and HEP for non‐idiopathic coronal angular deformity, as well as to identify clinical factors affecting correction velocity. Methods We retrospectively observed a consecutive series of patients with non‐idiopathic coronal angular deformity of the knee who underwent TH using HEP or TEP and completed the deformity correction process from July 2016 to July 2022. According to the kind of eight plates, we divided those patients into the HEP group and the TEP treatment group. Relevant clinical factors, including the mechanical lateral distal femoral angle (mLDFA), mechanical medial proximal tibial angle (mMPTA), screw divergence angle (SDA), angle of plate and screw (APS), hinge angle of HEP (HA), and the knee zone location of the lower extremity mechanical axis, were documented. Additionally, deformity correction velocity, complications, and clinical efficacy were assessed. Categorical variables were analyzed using the chi‐squared test, Fisher exact test, or Wilcoxon test, while continuous variables were evaluated using the t‐test or analysis of variance (ANOVA). Results There were 29 patients in the HEP treatment group (seven girls and 22 boys) and 33 patients (12 girls and 21 boys) in the TEP treatment group. In all, 91.86% (79/86 knees) of the genu angular deformities were completely corrected, 6.98% (6/86 knees) had the overcorrection condition, and 10.47% (9/86 knees) had screw loosening. The swayback HEP rate was 11.29% (7/62 HEPs), which was related to the screw loosening in the HEP group (p < 0.001). The overall correction velocities and screw divergence angle change speeds in the HEP group were all significantly faster than those in the TEP group (p < 0.05). The initial APS of the HEP implanted was higher than that of TEP (p < 0.01), and multisite changes of APS during deformity correction of the HEP group were smaller than that of the TEP group. Conclusion HEP proved to be an appropriate device for TH for non‐idiopathic coronal angular deformities of the knee with high correction velocity in children. Avoiding the occurrence of the swayback phenomenon may reduce the complications of HEP.